Rethinking deep renovation: The perspective of rental housing in Sweden. (10th September 2018) - Femenías, Paula; Mjörnell, Kristina; Thuvander, Liane
Abstract: This study examines renovation strategies among owners of rental housing in Sweden in response to European energy policies that promote deep renovation as a means to reduce carbon emissions from residential buildings. Case studies of ten housing companies, seven public and three private, were designed with the aim to examine housing owners' attitudes and renovation strategies, and how policies and objectives for energy efficiency become incorporated into these attitudes and strategies. Results are illustrated in typologies that distinguish between renovation strategies with either a more commercial or a more societal focus and spanning between deep and partial renovation. The typologies can be used to discuss how different aspects influence renovation, and illustrates how strategies change over time. The study identifies a trend in which housing owners are increasingly relying on partial or over-time renovation. Cost is one important driver, but social responsibility toward tenants and in some cases the protection of cultural heritage are also found to be important. A distrust of fixed models for renovation was observed. The paper questions the concept of deep renovation and suggests instead partial and over-time renovation as a way forward toward sustainable renovation. Partial renovation can bring together energy efficiency with environmental, financial, social, and cultural objectives of housing management. If managed properly, over-time renovation can reduce the risk of an investment, and has the advantage of allowing future technological advancements in energy efficiency to be included in current planning.